Would you believe ... the losers were killed in Mayan football? and other perilous pastimes - Platt, Richard 1953- (Would you believe ..., 2008)
This book helps young learners discover the story behind the games we play, examining the amazing peculiarities of international sport and leisure pursuits. Readers will learn about the wacky and often bloodthirsty games that our ancestors liked such as gladiatorial contests